Strategi Penagihan Piutang Yang Efisien dan Efektif (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to explore efficient and effective account receivable collection strategies in addressing delayed payments by customers. Using a qualitative approach, data were collected through in-depth interviews with internal company personnel. The findings indicate that payment delays are primarily caused by the unavailability of funds, as customers often await payments from third parties. The company addresses this isue by applying a soft approach and other adaptive strategies. This research contributes to the development of effective and contextual receivables collection strategies to maintain cash flow and sustain long-term business realtionships.